2006
DOI: 10.1007/s11199-006-9073-4
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents and Consequences of Perceived Personal Gender Discrimination: A Study of Solicitors in Hong Kong

Abstract: Informed by social identity theory, we developed a model to examine the antecedents and consequences of perceptions of personal gender discrimination. In the model, gender, gender identity, and perceived gender bias against women are considered as salient predictors of perceived personal gender discrimination, and organizational commitment and intentions to leave are considered as the outcome variables. Structural equation modeling (SEM) was used to analyze the data collected from a sample of practicing solici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 45 publications
(65 reference statements)
3
33
0
1
Order By: Relevance
“…To measure perceived climate of gender inequity, we used three items on a 5-point Likerttype scale, modified from Sanchez and Brock's (1996) scale and used in other studies examining this variable (Foley, Ngo, & Loi, 2006). The three items are as follows: 'At work, others make jokes or negative commentaries about women'; 'At work, I get the impression that being female may be a limitation'; and 'At work, I feel that others exclude women from some activities'.…”
Section: Perceived Climate Of Gender Inequitymentioning
confidence: 99%
“…To measure perceived climate of gender inequity, we used three items on a 5-point Likerttype scale, modified from Sanchez and Brock's (1996) scale and used in other studies examining this variable (Foley, Ngo, & Loi, 2006). The three items are as follows: 'At work, others make jokes or negative commentaries about women'; 'At work, I get the impression that being female may be a limitation'; and 'At work, I feel that others exclude women from some activities'.…”
Section: Perceived Climate Of Gender Inequitymentioning
confidence: 99%
“…Previous research has addressed different factors that may impede the perception of gender discrimination. These examined the costs of attributions to discrimination (Sechrist and Delmar 2009), the importance of schema activation in labelling organizational incidents as sexual harassment (Magley and Shupe 2005), the effects of sexist attitudes, personal beliefs, and gender identities of men and women in perceiving discrimination (Cameron 2001;Foley et al 2006) or protesting against it (Foster et al 2004), and the long-term consequences of coping with discrimination for well-being (Foster 2009). In the present research, we build on the observation made by Crosby and colleagues (1986), that failure to perceive gender discrimination at the individual level may be due to lack of group-level information (see also Rutte et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…According to Cox's (1994) interactional model of cultural diversity, the diversity climate of an organization affects individual affective and attitudinal reactions, including satisfaction. Past studies have indicated that perceptions of organizational prejudice and discrimination against one's ingroup are negatively associated with organizational attitudes including job satisfaction and organizational commitment (e.g., Ensher, Grant‐Vallone, & Donaldson, 2001; Foley, Ngo, & Loi, 2006; Foley, Ngo, & Wong, 2005; Gutek, Cohen, & Tsui, 1996; Redman & Snape, 2006). According to relative deprivation theory, when individuals feel they have less than they rightfully deserve, they are likely to feel and express dissatisfaction (Davis, 1959).…”
Section: Perceived Preference and Satisfaction With Managementmentioning
confidence: 99%
“…Several past studies have indicated that perceptions of organizational prejudice or discrimination against one's ingroup are negatively associated with organizational attitudes including job satisfaction and organizational commitment (e.g., Ensher et al, 2001; Foley et al, 2006; Foley et al, 2005; Gutek et al, 1996; Redman & Snape, 2006). In most cases, these researchers have discussed this relationship implicitly or explicitly in terms of perceived prejudice having a causal effect on organizational attitudes, as we have above.…”
Section: Perceived Preference and Satisfaction With Managementmentioning
confidence: 99%